Psychiatric morbidity and X-chromosomal origin in a Klinefelter sample - Boks, Marco P.M.; de Vette, Marjolein H.T.; Sommer, Iris E.; van Rijn, Sophie; Giltay, Jacques C.; Swaab, Hanna; Kahn, René S. (Schizophrenia research, 2007)
The presence of an additional X-chromosome in Klinefelter patients provides an opportunity to study the influence of this chromosome on psychiatric disorders. Previous studies have reported an excess of Klinefelter patients in psychiatric patient groups. We report an increased prevalence of psychiatric disorders including psychotic disorders in a sample of Klinefelter patients but could not find evidence of an effect of the parental origin of the extra X-chromosome on the psychiatric phenotype. Nevertheless, these findings provide further support for the role of the X-chromosome in the susceptibility to psychiatric disorders in general and psychotic disorders in particular.